A study on the subjectivity of female recreational sport participants' coaching experience: Q methodological approach - Wangsung Myung; Kwangho Park (Korea Institute of Sport Science, 2021)
Purpose The purpose of this study is to conduct a typological classification of female recreational sport participants' coaching experience. Methods Q methodology was conducted using 25 Q-samples and 25 P-samples. Data were analyzed using PQmethod software. Results Four types were categorized: communication and character-oriented (I), function and immersion-oriented (II), process and fun-oriented (III), and function and inclusion-oriented (IV). These types were re-categorized as 'non-functional value-oriented (I, III)' and 'functional value-oriented (II, IV)'. Conclusion This study also made efforts to explore the value and norm that female participants expect from sport participation, which provided a variety of perspectives on social, psychological and philosophical discussions about woman sport. In addition, each type and its characteristics can be used as meaningful basic data in teaching method (coaching theory) for woman sport.